2012
DOI: 10.1242/bio.20121263
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous and heterozygous GH transgenesis alters fatty acid composition and content in the liver of Amago salmon (Oncorhynchus masou ishikawae)

Abstract: SummaryGrowth hormone (GH) transgenic Amago (Oncorhynchus masou ishikawae), containing the sockeye GH1 gene fused with metallothionein-B promoter from the same species, were generated and the physiological condition through lipid metabolism compared among homozygous (Tg/Tg) and heterozygous GH transgenic (Tg/+) Amago and the wild type control (+/+). Previously, we have reported that the adipose tissue was generally smaller in GH transgenic fish compared to the control, and that the Δ-6 fatty acyl desaturase ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 52 publications
4
28
0
Order By: Relevance
“…The lower lipid content in a growth-enhanced transgenic fish is probably due to a higher rate of metabolism and increased requirements for energy, which results in increased rate of use of fat reserves. Sugiyama et al (2012) reported a significant beneficial influence of growth hormone transgenesis on liver fatty-acid composition in Amago salmon (Oncorhynchus masou ishikawae); thus transgenic fish had decreased contents of SFAs and MUFAs, as well as an increased content of PUFAs, among others EPA and DPA. The impact of an enhanced metabolism rate on lipid changes was also evident in the case of a transgenic tilapia (Oreochromis hornorum) containing foreign growth hormone, with a significantly reduced cholesterol concentration in its blood serum Martínez et al (1999).…”
Section: Modifications Of the Composition Of Milk Lipidsmentioning
confidence: 99%
“…The lower lipid content in a growth-enhanced transgenic fish is probably due to a higher rate of metabolism and increased requirements for energy, which results in increased rate of use of fat reserves. Sugiyama et al (2012) reported a significant beneficial influence of growth hormone transgenesis on liver fatty-acid composition in Amago salmon (Oncorhynchus masou ishikawae); thus transgenic fish had decreased contents of SFAs and MUFAs, as well as an increased content of PUFAs, among others EPA and DPA. The impact of an enhanced metabolism rate on lipid changes was also evident in the case of a transgenic tilapia (Oreochromis hornorum) containing foreign growth hormone, with a significantly reduced cholesterol concentration in its blood serum Martínez et al (1999).…”
Section: Modifications Of the Composition Of Milk Lipidsmentioning
confidence: 99%
“…The mean weights of the homozygous (Tg/Tg), heterozygous (Tg/+) (note that all the heterozygotes were produced using eggs from transgenic fish and sperm from wild type), and age control (+/+) fish used in this experiment were 131 g, 109 g, and 85 g, respectively. Details of the production and detection of the transgenic fish using PCR were described in a previous study (Sugiyama et al, 2012).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Extraction and purification of total lipids were performed following the method of Folch et al Fatty acid contents (mg/g) in muscle tissue from homozygous (black), heterozygous (gray) of GH transgenic amago salmon, and from controls (white), compared with those in liver tissue (Sugiyama et al, 2012). Contents of fatty acids were calculated using heptadecanoic acid (17:0) as an internal standard.…”
Section: Experimental Animalsmentioning
confidence: 99%
See 2 more Smart Citations